2022
DOI: 10.3389/fpsyg.2021.487039
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Experience of Social Change and Individualistic Parenting Goals Over Two Generations in Urban China

Abstract: During the past four decades, China has gone through rapid urbanization and modernization. As people adapt to dramatic sociodemographic shifts from rural communities to urban centers and as economic level rises, individualistic cultural values in China have increased. Meanwhile, parent and child behavior in early childhood has also evolved accordingly to match a more individualistic society. This mixed-method study investigated how social change in China may have impacted parenting goals and child development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…One possibility is that the tendency for children to overestimate themselves is widespread and relatively independent of cultural variation, which would be consistent with the view of selfoverestimation as a functional adaptation that benefits young children's learning and growth (Bjorklund & Beer, 2016;Shin et al, 2007). At the same time, it is also possible that individualistic trends have permeated modern-day China (and perhaps especially the urban areas where we conducted our research) to such an extent, that the Chinese children we tested have been exposed to quite similar norms and socialization messages as their Dutch counterparts-more than we anticipated at the outset of the research (Bian et al, 2022;Chen et al, 2005;Santos et al, 2017). Thus, while we consider our cross-cultural findings to be valuable, caution is needed in interpreting these findings.…”
Section: Discussionsupporting
confidence: 62%
“…One possibility is that the tendency for children to overestimate themselves is widespread and relatively independent of cultural variation, which would be consistent with the view of selfoverestimation as a functional adaptation that benefits young children's learning and growth (Bjorklund & Beer, 2016;Shin et al, 2007). At the same time, it is also possible that individualistic trends have permeated modern-day China (and perhaps especially the urban areas where we conducted our research) to such an extent, that the Chinese children we tested have been exposed to quite similar norms and socialization messages as their Dutch counterparts-more than we anticipated at the outset of the research (Bian et al, 2022;Chen et al, 2005;Santos et al, 2017). Thus, while we consider our cross-cultural findings to be valuable, caution is needed in interpreting these findings.…”
Section: Discussionsupporting
confidence: 62%
“…Other studies also reported that modernization fosters individualism (Han et al, 2020). Individualism has risen in urban Chinese society with the increase in urban residence, education level, divorce rate, and decrease in family size (Bian et al, 2022;Sun and Ryder, 2016). The impact of individualism is changing in different generations.…”
Section: Expectations Of Receiving Support Under Confucian Culturementioning
confidence: 98%
“…, 2020). Individualism has risen in urban Chinese society with the increase in urban residence, education level, divorce rate, and decrease in family size (Bian et al. , 2022; Sun and Ryder, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…( Bian et al, 2022 , English version (Cognitive aspects of informal education), 1982 , Greenfield et al, 2003 , Greenfield et al, 2019 , Rothstein-Fish, 2003 )…”
Section: Uncited Referencesmentioning
confidence: 99%